What are the defining characteristics of the most cited publications in orthognathic surgery?. Issue 11 (November 2018) - Susarla, S.M.; Tveit, M.; Dodson, T.B.; Kaban, L.B.; Hopper, R.A.; Egbert, M.A.
Abstract: The purpose of this study was to identify the characteristics associated with highly cited papers in orthognathic surgery. This was a cohort study of articles published in the English-language literature from 1900 to 2017. Citation databases were searched for papers related to orthognathic surgery and the most frequently cited papers were identified. For each paper, the following variables were collected: region of origin, time-period of publication, corresponding author specialty, journal of publication, topic area, study design, and number of citations. The outcome variable was the citation index (citations per year). North American investigators published 70% of the 100 most-cited articles in orthognathic surgery. The majority of papers were from oral and maxillofacial surgeons. Frequent content areas were diagnosis, virtual planning, fixation/stability, and complications. The majority (54%) of studies were cohort or case report/series. The mean number of citations was 235.0 ± 126.5; the mean citation index was 9.9 ± 6.1 citations per year. Time-period, content area, and study design were associated with the citation index (all P <  0.001). Time-period, content area, and study design predicted the citation index (all P  ≤ 0.009). Among frequently cited papers in orthognathic surgery, oral and maxillofacial surgeons had the highest volume of contributions. Diagnosis, treatment planning, and complications were the most common topics studied.